PT Pertamina's crisis communication strategy on the oil spill incident in Karawang - Husaini, Azis; Hidayat, Dadang Rahmat; Agustin, Herlina (Manajemen Komunikasi, 2025)
The oil spill on Karawang Beach has created an urgent need for an effective crisis communication strategy from PT Pertamina. This study describes Pertamina's approach to handling the oil spill incident, emphasizing rapid response, transparency, and open communication with various stakeholders. Through an in-depth analysis of the communication strategies implemented, this research aims to explain the specific steps taken by Pertamina to mitigate the impact of the oil spill on Karawang Beach, restore public trust in Pertamina, and enhance the company’s image. The findings of this study provide valuable insights for other companies facing similar situations and serve as a foundation for improving sustainability in crisis management and corporate communication. This incident had a national impact as the oil spread across three provinces: West Java, DKI Jakarta, and Banten. The research method used is descriptive qualitative with a case study approach, employing in-depth interviews and field observations. The results of this study show that Pertamina has already established standards for handling crisis communication, particularly concerning the government, mass media, and affected communities. Pertamina’s communication team divided tasks in managing information to prevent misinformation from spreading in the media. Additionally, Pertamina recognized that managing stakeholder communication during this incident required continuous adjustments to its communication strategy methods.